The effect of vermicularity on the thermal conductivity of vermicular graphite cast iron. (5th March 2016) - Ma, Z.J.; Tao, D.; Yang, Z.; Guo, Y.C.; Li, J.P.; Liang, M.X.; Li Yeung, Lugee T.
Abstract: As an ideal material for the cylinder head of high power density diesel engine, vermicular graphite cast iron (VGI) with higher thermal conductivity was received more and more attention recently. In this article, finite element (FE) software ANSYS was applied to investigate the changes of thermal conductivity of VGI with the vermicularity and the FE-models are carried out based on the real metallographic images of VGI. The results indicate that there is a big difference between the numerical simulation and the reality without the consideration of the thermal contact resistance of interface between matrix and graphite. The numerical simulation result is close to the reality when the contact thermal conductance is set at 0.1 W/(m 2 ·K). In addition, the equivalent thermal conductivity along X direction k equ, x rises from 34.437 W/m·K to 38.902 W/m·K and increases by 13% or so when the vermicularity is improved from 40% to 90% according to the numerical simulation. Graphical abstract: Highlights: Interfacial thermal contact resistance affects the thermal transfer of cast iron obviously. Interfacial thermal contact resistance is about 0.1 W/(m 2 ·K). The thermal conductivity of cast iron can be predicted by finite element model with relatively high accuracy.